Compound heterozygous null mutations of NOBOX in sisters with delayed puberty and primary amenorrhea. Issue 10 (4th September 2021) - Sassi, Asma; Désir, Julie; Duerinckx, Sarah; Soblet, Julie; Van Dooren, Sonia; Bonduelle, Maryse; Abramowicz, Marc; Delbaere, Anne
Abstract: Background: Premature ovarian insufficiency (POI) is a heterogeneous clinical syndrome defined by a premature loss of ovarian function that associates menstrual disturbances and hypergonatropic hypogonadism. POI is a major cause of female infertility affecting 1% of women before the age of 40 and up to 0.01% before the age of 20. The etiology of POI may be iatrogenic, auto‐immune or genetic but remains however undetermined in a large majority of cases. An underlying genetic etiology has to be searched in idiopathic cases, particularly in the context of a family history of POI. Methods: Whole exome sequencing (WES) was performed in trio in a Belgian patient presenting POI and in her two parents. The patient presented delayed puberty and primary amenorrhea with hypergonadotropic hypogonadism. Results: WES identified two novel compound heterozygous truncating mutations in the Newborn oogenesis homeobox ( NOBOX ) gene, c.826C>T (p.(Arg276Ter)) and c.1421del (p.(Gly474AlafsTer76)). Both mutations were confirmed by Sanger sequencing in the proband's sister who presented the same phenotype. Both variants were pathogenic and very likely responsible for the severe POI in this family. Conclusion: We report here for the first time compound heterozygous truncating mutations of NOBOX in outbred patients, generalizing biallelic NOBOX null mutations as a cause of severe POI with primary amenorrhea. In addition, our findings also suggest that NOBOX haploinsufficiency is tolerated. Abstract : Two novel compound heterozygous NOBOX mutations were identified by WES in two sisters presenting primary amenorrhea and hypergonadotropic hypogonadism. These findings validate that biallelic NOBOX null mutations induce a severe phenotype of premature ovarian insufficiency, expanding its contribution to the development of the syndrome.